2020
DOI: 10.1055/s-0040-1715814
|View full text |Cite
|
Sign up to set email alerts
|

Combined Tissue Transfer for Extensive Lower Limb Complex Defects: Flow-through Flaps, Chimera, and “Orochi” Flaps

Abstract: Perforator flaps can be raised anywhere in the body, with minimal donor-site deformity, and can be made into custom-made combined composite flaps, especially for severe complex defects such as osteomyelitis of the lower limbs. Here, we report on the representative application of the combined tissue transfers for complex leg defects. For a wide range of complex defects in the lower extremity, it is necessary to perform reliable revascularization by bypass or flow-through type or vein graft. At the same time, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…There have been advances in minimally invasive free perforator flap procedures for complex wounds. 25 Lower limb revascularization has been increasing in popularity for endovascular intervention owing to less invasiveness than bypass surgery, which was also corroborated by our result. However, bypass surgery is superior to endovascular intervention for long-term primary patency 26 ; further, Hsu et al have found that there was no significant difference in flap failure or limb salvage rate regarding the difference in revascularization between free flap reconstruction.…”
Section: Discussionsupporting
confidence: 88%
“…There have been advances in minimally invasive free perforator flap procedures for complex wounds. 25 Lower limb revascularization has been increasing in popularity for endovascular intervention owing to less invasiveness than bypass surgery, which was also corroborated by our result. However, bypass surgery is superior to endovascular intervention for long-term primary patency 26 ; further, Hsu et al have found that there was no significant difference in flap failure or limb salvage rate regarding the difference in revascularization between free flap reconstruction.…”
Section: Discussionsupporting
confidence: 88%
“…This method can provide reconstruction for damaged vessels less than 20 cm in length, combining large skin defects within 30 × 15 cm. One of the disadvantages is there is a risk of necrosis of both the ALT flap and distal extremity (Koshima, 2021). In our cohort, the ALT flap was chosen for soft tissue coverage, particularly since it allowed for vascular reconstruction with a flow‐through style or an extravascular segment for grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported more favorable outcomes after successful revascularization than revision amputation with prosthetic rehabilitation (Pet et al, 2016). Reconstruction of the upper extremity remains the optimal choice for patients facing such traumatic circumstances (Fernandez‐Garrido et al, 2019; Koshima, 2021).…”
Section: Introductionmentioning
confidence: 99%